Discursive strategies in psychoeducational consultation: a sociocultural reading of empirical evidence - Soto González, Rodolfo (2022)
Collaborative consultation processes are communicative and conversational processes in whose development the discursive strategies used by the consultants play a critical role. Although empirical studies have identified some of these strategies, it is necessary to move towards a more articulated and conceptually coherent reading of the role of these strategies in consultation processes. This essay aims to contribute to this reading, based on a sociocultural approach to consultation processes. The proposition of this essay is to develop an organizing scheme inspired by this sociocultural approach, which would read the discursive strategies identified by the research. We identified 14 discursive strategies in the current body of empirical evidence. In the organizing scheme we propose, these strategies are located within the framework of the process of construction of shared meanings among participants, distinguishing between listening discursive strategies (at the service of the construction of an initial level of intersubjectivity) and influence discursive strategies (at the service of the subsequent negotiation of meanings). We conclude that the proposed organizing scheme can constitute a useful tool, both conceptually and to guide the strategic use of discursive strategies in the consultants’ practice and the training processes for such professionals.